Level of nurses’ knowledge concerning prevention of hospital-acquired infections in surgical wards - Sierpińska, Lidia; Jaworski, Sebastian (Journal of Education, Health and Sport, 2022)
Introduction. Prevention of hospital-acquired infections in surgical wards is associated with a high level of nurses’ knowledge and skills in the area of the observance of procedures, standards of prevention of infections, use of personal protection means, and isolation of patients infected with the alert pathogen. Objective. The aim of the study was recognition of the level of knowledge concerning prevention of hospital-acquired infections among nursing staff in surgical wards. Materials and Method. The study was conducted in 2021, and included 115 nurses employed in hospital wards in two hospitals. The research method was a diagnostic survey, the technique – a questionnaire, and the research tool – an author-constructed questionnaire. Results. The majority of the examined nurses (68.0%) presented a ‘mediocre’ level of knowledge concerning hospital-acquired infections, while 38.9% - a ‘low’ level. More than a half of the respondents (60.0%) knew the purpose for hygienic handwashing. Approximately ¾ of respondents knew that there is no necessity for using sterile gloves during procedures related with the risk of contact with blood or body fluids. The majority of nurses in the study (62.5%) had a deficit of knowledge about transient flora inhabiting the skin, and 1/3 of respondents had no established principles of observance of personal protection means. More than a half of nurses (65.2%) did not know the objective of isolation of patients infected with an alert pathogen. Nearly a half of respondents (47.8%) knew that standard isolation is applied in each patient, irrespective of the previous medical history taking. Almost 2/3 of respondents (64.3%) knew that isolations applied in infections transmitted through contact, by airborne-droplet and airborne-dust routes are the types of above-standard isolation. Conclusions. The results of the study confirm the need for expanding the scope of knowledge about prevention of hospital-acquired infections, the time of hygienic and surgical handwashing, as well as the principles of using personal protection means. The nurses presented a deficit of knowledge concerning transient flora of pathogenic microorganisms inhabiting the surface of the hands, and the principles of using personal protection means. Nurses require the expansion of the scope of knowledge about the goal and principles of standard and above-standard isolation of patients infected with alert pathogen.